The Impact of Flipped Classroom-Based Problem-Based Learning (PBL) on Student Learning Outcomes in Islamic Religious Education at SMA Negeri 1 Koto Baru, Dharmasraya Regency - Ikbal, Ahmad (Ruhama : Islamic Education Journal, 2025)
The global challenge in Islamic Religious Education (PAI) lies in the persistent use of passive, lecture-based methods that fail to foster critical thinking or real-world application of Islamic values, particularly in addressing contemporary moral dilemmas like digital fitnah (temptation) (Halstead, 2004; Klein et al., 2023). This study aims to bridge this gap by evaluating the efficacy of a Flipped Classroom-based Problem-Based Learning (FC-PBL) model in enhancing cognitive and spiritual competencies in PAI. Using a quasi-experimental design with pretest-posttest controls, two groups of Grade X students at SMAN 1 Koto Baru were compared: the experimental group (FC-PBL, *n*=33) and the control group (traditional instruction, *n*=33). Data were analyzed via N-Gain scores, t-tests, and ANCOVA. Results revealed a 19% N-Gain disparity (74% experimental vs. 55% control), with the FC-PBL group showing superior posttest scores (Mean=13.03 vs. 11.12), higher engagement (96.67% high-category scores), and mastery of ethical concepts like zina prohibitions (*p*=0.000). The FC-PBL model’s synergy—combining self-paced pre-class learning (Flipped Classroom) and collaborative problem-solving (PBL)—validates its alignment with constructivist theory and cognitive load optimization. Limitations include the single-school sampling and short intervention duration, suggesting the need for longitudinal, multi-site replication. This study offers a transformative blueprint for modernizing Islamic education globally.